A Systematic Assessment of Google Search Queries and Readability of Online Gynecologic Oncology Patient Education Materials. - Martin, Alexandra; Stewart, J. Ryan; Gaskins, Jeremy; Medlin, Erin (Journal of Cancer Education, 2019)
The Internet is a major source of health information for gynecologic cancer patients. In this study, we systematically explore common Google search terms related to gynecologic cancer and calculate readability of top resulting websites. We used Google AdWords Keyword Planner to generate a list of commonly searched keywords related to gynecologic oncology, which were sorted into five groups (cervical cancer, ovarian cancer, uterine cancer, vulvar cancer, vaginal cancer) using five patient education websites from sgo.org . Each keyword was Google searched to create a list of top websites. The Python programming language (version 3.5.1) was used to describe frequencies of keywords, top-level domains (TLDs), domains, and readability of top websites using four validated formulae. Of the estimated 1,846,950 monthly searches resulting in 62,227 websites, the most common was cancer.org . The most common TLD was *.com. Most websites were above the eighth-grade reading level recommended by the American Medical Association (AMA) and the National Institute of Health (NIH). The SMOG Index was the most reliable formula. The mean grade level readability for all sites using SMOG was 9.4 ± 2.3, with 23.9% of sites falling at or below the eighth-grade reading level. The first ten results for each Google keyword were easiest to read with results beyond the first page of Google being consistently more difficult. Keywords related to gynecologic malignancies are Google-searched frequently. Most websites are difficult to read without a high school education. This knowledge may help gynecologic oncology providers adequately meet the needs of their patients.